Identifying public transport gaps using time-dependent accessibility levels. (October 2015) - Fransen, Koos; Neutens, Tijs; Farber, Steven; De Maeyer, Philippe; Deruyter, Greet; Witlox, Frank
Abstract: One of the concerns that has aroused much scholarly attention in transport geography lately is the extent to which public transport provision enables the less privileged population segments, especially those without privately owned motorized vehicles, to participate in activities that are deemed normal within the society they live in. This study contributes to this line of inquiry by proposing a methodology for identifying public transit gaps, a mismatch between the socially driven demand for transit and the supply provided by transit agencies. The methodology draws on the latest accomplishments in the field of modeling time-continuous, schedule-based public transport accessibility. Accessibility levels to key destinations are calculated at regular time intervals, and synoptic metrics of these levels over various peak and off-peak time windows are computed for weekdays and weekends. As a result, a temporally reliable picture of accessibility by public transport is constructed. The obtained index of public transport provision is compared to a public transport needs index based on the spatial distribution of various socio-demographics, in order to highlight spatial mismatches between these two indices. The study area consists of Flanders, which is the northern, Dutch-speaking region of Belgium. The results indicate that mainly suburban areas are characterized by high public transport gaps. Due to the time-variability of public transport frequencies, these gaps differ over time. Highlights: Inadequate or lack of mobility can contribute to social disadvantage and exclusion. A time-continuous and schedule-based approach was applied to identify transit gaps. Multimodal access to key destinations at regular time intervals was computed. Transit need and provision were compared to determine the geographical disparities. The gaps in public transport are pinpointed for the region of Flanders, Belgium.